Efficacy of 5-aminolevulinic acid based photodynamic therapy in pituitary adenomas: experimental study on rat and human cell cultures - Neumann, Lisa Margarete; Hänggi, Daniel (Photodiagnosis and photodynamic therapy, 2016)
Background - Incomplete resection of pituitary adenomas may result in recurrence. As adjuvant irradiation is not riskless, alternative treatment options should be investigated. 5-aminolevulinic acid based photodynamic therapy (5-ALA based PDT) showed promising results for malignant gliomas. The present study examined the efficacy of 5-ALA PDT in vitro on benign pituitary adenoma cell cultures. - Methods - In group I experiments were performed on immortalized rat pituitary adenoma cells (GH3). The cultured cells were treated with different 5-ALA concentrations ranging from 7.5-16.5μg/ml. In Group II human pituitary adenoma cell cultures were obtained from surgically resected adenoma tissue (n=15). These were incubated with 5-ALA concentrations from 12.5-100μg/ml. The concentration ranges had been determined in preliminary dose-finding tests. For both groups incubation time was four hours and PDT was performed by exposition to laser light (635nm, 625s, 18.75J/cm2). Cell viability was examined by WST-1 assay. - Results - In both groups PDT showed a 5-ALA concentration-dependent effect on cell death. In group I lower 5-ALA concentrations were necessary to destroy all cells as compared to group II. Moreover, in group II, the different subtypes of human adenomas showed different sensitivities to 5-ALA-based PDT (secreting vs. non-secreting). Especially corticotroph adenomas were highly sensitive to 5-ALA PDT. - Conclusions - The GH3 cell line was an useful in vitro model to optimize different PDT parameters. Human pituitary adenoma cells could also be killed by 5-ALA PDT, however this required higher 5-ALA concentrations. Furthermore, the results suggested different 5-ALA sensitivities between different human adenoma cell types. More experiments are necessary to confirm these preliminary results.
Gesehen am 25.06.2019